Towards a dynamic object-oriented design metric plug-in framework - Loh, Chuan Ho; Lee, Sai Peck (2008)
Problem Statement: The evolution of software is made difficult by the need to integrate new features with all previously implemented features in software applications. Approach: present study introduced a general-purpose, platform-independent object-oriented design metric plug-in framework called jmetric intended to help building scalable, extendable object-oriented design metric plug-ins. jmetric seeks to address problem by providing the plug-in developer a structured way to separately develop and incrementally integrate independent object-oriented design metrics as plug-ins to a domain specific object-oriented design metrics framework. jmetric was engineered to provide functional building blocks to accelerate the adding, removing and updating of object-oriented design metric plug-ins in tools such as Eclipse, JDeveloper, NetBeans, JBuilder and other Java-based tools. Dependency injection is heavily used in jmetric to accelerate the adding, removing and updating of object-oriented metrics plug-ins. We studied several commonly used integrated development environments and software metrics tools to identify the extendibility of the tools to provide additional object-oriented design metric functionalities as plug-ins. Results: We demonstrate a tool called jmetric tool that had developed as a reference implementation to validate the plug-in capabilities of jmetric. Conclusion: Extending other tools such as Eclipse, JDeveloper and NetBeans to include metric functionalities is possible by wiring plug-ins through dependency injection mechanism in jmetric.